Pengaruh Gaya Kepemimpinan dan Stres Kerja Terhadap Turnover Karyawan PT. Tirta Osmosis Karyawan - Lestari, Yeyen; Yustini, Tien; Halin, Hamid (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This research aims to determine whether leadership style and work stress affect employee turnover at PT. Tirta Osmosis Sampurna. This research employs a quantitative approach. Data collection involves questionnaires. The population and sample consist of 70 respondents. The data analysis techniques include validity test, reliability test, classical assumption test consisting of normality test, multicollinearity test and heteroscedasticity test, multiple regression analysis test, hypothesis testing consisting of t-test, f-test and coefficient of determination. The results of data analysis indicate that there is a significant influence between the independent variable, leadership, on the dependent variable, turnover. This is indicated by the t-count value of leadership of 14.404 > t table value of 1.995 with a significance value of 0.000 < 0.05, and the t-count value of work stress of 0.675 > 1.995 with a significance value of 0.502 > 0.05, with R² having a value of 0.797. The work stress variable does not significantly affect the turnover rate. The magnitude of the influence of leadership and work stress variables simultaneously is 79.7% on turnover. The remaining 20.3% is influenced by other variables not examined. These findings highlight the critical role of effective leadership in minimizing employee turnover within the company.